2013
DOI: 10.1016/j.jocn.2012.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal visual search in a large field by patients with unilateral spatial neglect

Abstract: Abstract:In this study, we investigated the horizontal visual search ability and pattern of horizontal visual search in a large space performed by patients with unilateral spatial neglect (USN). Subjects included 9 patients with right hemisphere damage caused by cerebrovascular disease showing left USN, 9 patients with right hemisphere damage but no USN, and 6 age-matched healthy individuals with no history of brain damage.The number of visual search tasks accomplished was recorded in the first experiment, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…In a previous study, we reported a strong correlation between the number of visual search tasks accomplished in a large space and the total BITC score, and no significant difference was observed in the neck rotation angle as well as the average and maximum values of the group without USN including normal healthy adults and individuals with USN, under experimental settings [7]. In addition, the neck rotation pattern of the group with USN presented a tendency to search in the right space [7]. In this experimental setting, the non-USN group with right hemisphere damage and healthy adult group obtained the highest score (36 points) in the visual search task in a large space.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…In a previous study, we reported a strong correlation between the number of visual search tasks accomplished in a large space and the total BITC score, and no significant difference was observed in the neck rotation angle as well as the average and maximum values of the group without USN including normal healthy adults and individuals with USN, under experimental settings [7]. In addition, the neck rotation pattern of the group with USN presented a tendency to search in the right space [7]. In this experimental setting, the non-USN group with right hemisphere damage and healthy adult group obtained the highest score (36 points) in the visual search task in a large space.…”
Section: Discussionmentioning
confidence: 79%
“…By analyzing horizontal visual search ability, head position, and neck rotation pattern during the search task in a large space, we reported a strong correlation between the number of visual search tasks performed in a large space and the total BITC score. Furthermore, no significant difference was observed with respect to the neck rotation angle as well as the average and maximum values of the two groups [7].…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…Individuals with USN tend to compensate visual search capability and achieve balance on the neglected side with cervical rotations (6,7). Spatial and temporal patterns of visual search during cancellation, visuomotor, and visual search tasks have been proposed to improve (8).…”
Section: Introductionmentioning
confidence: 99%